Unemployment Challenge and Labor Market Participation of Arab Gulf Youth: A Case Study of the UAE - Anita Poplavskaya (15445445) (2023)
The goal of the study is to explore the unemployment challenge for the United Arab Emirates (UAE) youth in comparison with other Gulf countries. The chapter uses multiple data sources to provide a complex analysis of recent dynamics and the current situation of school-to-work transition among Emirati youth. The empirical part of the analysis provides the rear information on actual career paths and challenges for youth to find their first job. Skills shortages and lack of professional qualities are among the frequently named reasons for not getting a job. For young women, such obstacles as family responsibilities and geographical restriction of job search are reported. Young men find jobs much faster than women. The main channels of job search for the Emiratis are personal liaisons and university contacts. Other Information Published in: Social Change and Transformation in the Gulf Region License: https://creativecommons.org/licenses/by/4.0 See chapter on publisher's website: https://dx.doi.org/10.1007/978-981-19-7796-1_30